Peredaran Ilegal Obat Aborsi melalui Media Sosial dan Upaya Penanggulangannya - Adhika Primananda; Dewa Gede Bayu Rastika (Badan Pengawas Obat dan Makanan, 2021)
The stigmatization and the strict rules of the abortion practice makes Indonesian women often seek help for abortion through non-medical personnel or by using misoprostol privately without prescription. Difficult to access the information, interactions, and transactions in the real world, coupled with the adherence of teenagers' lives to the social media, can encourage teenagers who experience unwanted pregnancies to overcome their problems from the real world to the cyberspace. This phenomenon is exploited by irresponsible persons by promoting and illegally distributing drugs that are claimed as abortion drugs. This study aims to describe the condition of the illicit trafficking of illegal abortion drugs in social media and find the best intervention that can be done to solve the problem. This study was conducted by collecting and processing big data sourced from social media using Netlytic application and then analyzing the data using the Problem Analysis Triangle concept. Interesting findings from social media analysis is that abortion drug sellers use an intimate approach to target those teenagers. They try to build intimate, trusted, interactive and communicative interaction with the potential clients by using words such as “school” and provide suggestions of drug use according to the age of the pregnancy. The illicit trafficking of illegal abortion drugs through social media that is carried out conspicuously and widely with a high amount of seller shows that there is an opportunity that motivates the prepetrators who illegally sells abortion drugs because of the absence of guardian that capable to guard the market. Therefore, it is necessary to intervene the sellers of illegal abortion drugs as criminals (offenders), consumers of abortion drugs as targets (targets/victims), and the market in the form of social media as a place of crime (Place) to prevent the crime and victimization from happening.